EVALUATION OF THE IMPACT OF THE SHARIA MINI BANK LABORATORY ON STUDENT COMPETENCE - Yoesoef, Yoesrizal Muhammad; Hayati, Husna; Khairisma, Khairisma; Syarif, Muhammad Fazlurrahman (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
This study aimed to provide an overview concerning the role of the Islamic mini bank laboratory in improving student competence. A qualitative methodology was used comprising field observations, interviews, and document analysis. The results showed that there is a need for improved facilities, additional management members, and public-oriented promotions. Four empowerment models for Islamic mini bank laboratory were identified, with the fourth stage being the most effective in the context of